2006
DOI: 10.1097/01.mlg.0000230440.83375.4b
|View full text |Cite
|
Sign up to set email alerts
|

General and Rhinosinusitis‐Related Quality of Life in Patients With Wegener's Granulomatosis

Abstract: Sinonasal involvement impacts significantly on the general QOL of patients with WG and is at least as significant as that of the general rhinosinusitis population. Nasal symptoms that are of particular relevance to this patient group include nasal crusting and epistaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 7 publications
4
41
1
2
Order By: Relevance
“…The Royal College of Surgeons of England used the SNOT 22 questionnaire extensively in a National comparative audit of surgery for nasal polyposis and chronic rhinosinusitis. It has also been used as a measure of outcome after septal surgery [20], polypectomy [21] or in patients with Wegener's granulomatosis [22]. It can be completed quickly and easily even in an outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…The Royal College of Surgeons of England used the SNOT 22 questionnaire extensively in a National comparative audit of surgery for nasal polyposis and chronic rhinosinusitis. It has also been used as a measure of outcome after septal surgery [20], polypectomy [21] or in patients with Wegener's granulomatosis [22]. It can be completed quickly and easily even in an outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the chronic morbidity observed in patients with AAV, there is little known about how disease manifestations affect HRQOL. Small single‐center studies examining what variables influence HRQOL have suggested that lung damage, joint involvement, and sinonasal involvement have each been potentially important determinants of physical components of HRQOL in different studies (5–7). Determining which disease manifestations influence HRQOL and in what domains they affect HRQOL may help focus treatment for patients with AAV and help evaluate newer therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, the performance of the SF-36 had not been formally evaluated as an outcome measure in AAV. Both clinical practice and trial data consistently demonstrate that HRQOL is impaired among patients with AAV 24,25,31,32,33,34 .…”
Section: Core Set Domain: Patient-reported Outcomes: Health-related Qmentioning
confidence: 87%